KRITIK SASTRA MELALUI PANDANGAN FEMINISME DALAM NOVEL SI CANTIK DAN SANG PEMBERANI KARYA ATIKAH SOLIHAH - Mulasih; Sulistiyono; AR, Muhammad Misbahudholam (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The modern world requires a wider perspective in life, one of which is about feminism which is a representation of gender equality, more specifically to fight discrimination against women. This study was used to examine one of children's book entitled, "Si Cantik dan Sang Pemberani " by Atikah Solihah with a qualitative descriptive method. The results show that the book describes of patriarchal cultures such as imposing the role of housewives, subordination of women, and depictions of women who are considered irrational, and toxic masculinity. Then the culture was destructed by the fact that the character, Pongota, which is a woman, managed to play two roles at once, between the feminine world (cooking and weaving) to the masculine world (war and self-defense), then met Sangarlang, a man who respects women and is not afraid of his self-esteem being destroyed just because Pongota is that great.